A retrospective study on magnetic resonance imaging findings in knee injuries - Dosita, E.; Ramesh, M. (International Journal of Research in Orthopaedics, 2025)
Background: Magnetic resonance imaging (MRI) is a noninvasive and accurate tool for diagnosing internal knee injuries after trauma. It reliably detects anterior cruciate ligament (ACL) tears, meniscal injuries, collateral ligament damage, and bone contusions, which often coexist in traumatic knee injury. This study aimed to evaluate the prevalence and types of MRI-detected knee injuries and their associations with patient age and gender. Methods: This retrospective observational study included 132 patients who underwent knee MRI following trauma at a radiology department. Patients of all ages and genders were included unless their MRIs showed only degenerative changes or incomplete data. MRI reports were reviewed for ligamentous injuries [ACL, posterior cruciate ligament (PCL), medial collateral ligament (MCL), and lateral collateral ligament (LCL)], meniscal tears, and bone contusions. Data on age and gender were recorded and analysed. Results: Among 132 patients, 70.45% were male and 29.55% were female, with the largest age groups being 21-30 years (30.3%) and 41-50 years (31.82%). ACL injuries were present in 78.78% of cases, meniscus injuries in 61.36%, PCL injuries in 39.39%, bone contusions in 14.39%, MCL injuries in 8.33%, and LCL injuries in 3.78%. Complete ACL tears accounted for 41.35% of all ACL injury cases. Significant associations were found between age and ACL injury (p=0.002), meniscus injury (p=0.001), bone contusion (p=0.046), and LCL injuries (p=0.044). No significant differences were observed between gender for any injury type. Conclusions: Our study highlights MRI's effectiveness in detecting and classifying traumatic knee injuries. ACL tears, often accompanied by meniscal and PCL injuries, were the most common. Injury patterns varied with age but not gender, emphasising MRI’s role in early diagnosis and age-specific management.